2017
DOI: 10.18857/jkpt.2017.29.3.128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plank Exercises with Hip Abduction Using Sling on Trunk Muscle Activation in Healthy Adults

Abstract: Purpose: The purpose of this study is to investigate the effects of healthy persons performing a plank exercise with hip abduction and use of sling on trunk muscle activity. Methods: Twenty-three subjects participated in this study. Muscle activities of the multifidus, rectus abdominis, external oblique and internal oblique were assessed with electromyography (EMG) while the subjects performed 6 various types of plank exercises in random order.Results: There was a significant difference in multifidus and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(11 reference statements)
0
6
1
3
Order By: Relevance
“…Although the exercises were not the same as the present study, a previous study indicated that the muscle activities of the ipsilateral GM, erector spinae, and contralateral latissimus dorsi muscle on the unstable side, i.e., the side with the hip joint extended, were increased by the prone hip extension exercise [31]. Another study show that in a variety of flat support motions, in sling training for ankle support, the activity of trunk muscles was significantly increased [32]. In this study, during the leg-lifting with flat support exercise, the unstable side was supported by an unstable surface.…”
Section: Discussioncontrasting
confidence: 48%
“…Although the exercises were not the same as the present study, a previous study indicated that the muscle activities of the ipsilateral GM, erector spinae, and contralateral latissimus dorsi muscle on the unstable side, i.e., the side with the hip joint extended, were increased by the prone hip extension exercise [31]. Another study show that in a variety of flat support motions, in sling training for ankle support, the activity of trunk muscles was significantly increased [32]. In this study, during the leg-lifting with flat support exercise, the unstable side was supported by an unstable surface.…”
Section: Discussioncontrasting
confidence: 48%
“…After analyzing titles and abstracts, 146 potentially relevant studies were selected. After analysis of the full texts, 13 studies are considered eligible and are included for further analysis: [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30].…”
Section: )Data Collection Processmentioning
confidence: 99%
“…가로면에서의 회전 운동은 몸통 중심 안정화에 특화 된 기능 훈련으로 점진적으로 더 큰 저항과무게를 주어 시행한다 (Akuthota et al, 2008). 몸통 회전 저항운동 기 구(torso rotation machine)는 기구를 잡은 팔이 레버의 역할을 하며 회전중심축에서 몸통 회전 힘을 토크로 변환하여 거리가 멀수록, 저항 부하가 클수록 더 강한 표면근의 근력을 요구하게 된다 (Bak et al, 2017). 특히 가로면에서의 저항운동은 배 주변 근육을 강화하여 몸 통 안정성을 유지하는데 큰 도움이 된다 (Akuthota et al, 2008 (Liebenson et al, 2009).…”
Section: ⅰ 서 론unclassified